Construction of the Radicalism Meaning in Society - Hafidh Maksum; Sulaiman Sulaiman; Rusli Yusuf; Misri A Muchsin; Deny Setiawan (Universitas Serambi Mekkah, 2022)
This research discusses the construction of the radicalism meaning in the people of Gampong Bueng Bakjok, Aceh Besar district. This study aims to reveal the perspective of the Gampong Bueng Bakjok Community regarding the meaning of radicalism and the link between the understanding of radicalism in society. Using qualitative research methods, where researchers directly observe the people being studied and try to analyze objective and subjective experiences. The key informants in this study were the people of Gampong Bueng Bakjok. because they are considered representative and have the capacity to answer problems. While the supporting informants were community leaders in Gampong Bueng Bakjok, who immediately became role models for the community. Analysis of the data was carried out using Peter L. Berger's theory of social construction which looks at three main factors of construction; externalization, objectivation and internalization. The results of this study reveal that the understanding of radicalism in society is divided into 4 parts, radicalism has the meaning of creating chaos and violence; thinks himself most righteous; critical and hard in preaching; rude in social interaction and prejudice with other than the group or class. The article recommends that community leaders and community observers use the results of this research to prevent the dangers and misunderstandings of the construction of the meaning of radicalism, especially for the community. Keywords: Construction, Radicalism, Society